The Effects of Cognitive-Based Interventions in Older Adults: A Systematic Review and Meta-Analysis - Sunweon Yun; Seang Ryu (Tehran University of Medical Sciences, 2022)
Background: Cognitive-based intervention is divided into three types: Cognitive Stimulation (CS), Cognitive Training (CT), and Cognitive Rehabilitation (CR). This study was conducted to identify systematically the effects of cognitive-based interventions in randomized controlled trials (RCTs) applied to older adults in the following three groups: cognitively healthy, mild cognitive impairment (MCI), and dementia. Methods: This search was carried out using the Ovid-MEDLINE, EMBASE, Cochrane library, CINAHL, ProQuest, and Korea databases. The effectiveness of the intervention was verified using the CMA 2.0 program. Results: A total of 54 RCTs were included in systematic reviews and 38 studies were analyzed by meta-analysis. Meta-analysis showed that cognitive-based interventions were effective in improving the cognitive function (SMD=0.39, 95% CI=0.32-0.44) of older adults. The subgroup analysis of cognitive function revealed that CT was the most effective in the cognitively healthy (SMD=0.40, 95% CI=0.33-0.46) and the MCI (SMD=0.45, 95% CI=0.27-0.63) groups, and CS was the most effective in the dementia group (SMD=0.57, 95% CI=0.43-0.70). Conclusion: In order to improve the cognitive function of older adults in each group, the most effective intervention type needs to be considered first. Evidence on the appropriate type of Cognitive-based intervention will be helpful in nursing practice.